Effect of ageing on the microstructure of reclaimed asphalt binder with bio-based rejuvenators. Issue 7 (3rd October 2019) - Cavalli, M. C.; Partl, M. N.; Poulikakos, L. D.
Abstract : Reclaimed asphalt pavement (RAP) has become an important source in asphalt pavement production for energy and cost savings. In this work, three different bio-based rejuvenators were added to the RAP binder: a vegetable oil, a cashew nut shell-based oil and a tall-based oil. Saturates-aromatics-resins-asphaltenes (SARA) analysis was performed to observe the evolution of different chemical fractions before and after ageing. Results suggested changes in chemical fractions after the addition of the rejuvenators; specifically a decrease of polar compounds. To better understand the binders' morphology, atomic force microscopy (AFM) was used for topography investigation and phase detection. RAP binder morphology was significantly affected by the addition of rejuvenators. Furthermore, ageing had an effect not only at polar and non-polar fractions level but also at microstructural level. Aim of this work was to show how the addition of rejuvenators affected both the microstructure and the chemical fractions of RAP binder before and after ageing. Such evaluation can help developing guidelines for evaluating the rejuvenating effect in the RAP binder.